Comparative analysis of the training programs of female skiers in the preparatory period of the annual training cycle - Stovba, I.; Stolyarova, N.; Petrozhak, O. (Advances in Health Sciences Research, 2019)
Continuous improvement of the training process in various groups and sports disciplines determines the current status of sports training. Research in sports plays an important role. Such research is aimed at establishing the relationship between the dynamics of the athlete`s status and training loads in the annual training cycle [1, 2]. Increasing results, increasing economic costs, the difficulty of providing training with equipment urgently require an intensive search for optimal ways to structure sports training, which allows achieving high sports results by improving sports training methods [3]. The article describes the features of the training programs of ski-racers. The experiment involved athletes of various qualifications with similar sports experience. The main parameters of the training process in both groups practically did not differ. In the experimental group, adjustments were made to the training program, as well as indicators were determined for step-by-step control.